Long-term effectiveness of unboosted atazanavir plus abacavir/lamivudine in subjects with virological suppression: A prospective cohort study. Issue 40 (October 2016) - Llibre, Josep M.; Cozzi-Lepri, Alessandro; Pedersen, Court; Ristola, Matti; Losso, Marcelo; Mocroft, Amanda; Mitsura, Viktar; Falconer, Karolin; Maltez, Fernando; Beniowski, Marek; Vullo, Vincenzo; Hassoun, Gamal; et al.
Abstract : Abstract: Effectiveness data of an unboosted atazanavir (ATV) with abacavir/lamivudine (ABC/3TC) switch strategy in clinical routine are scant. We evaluated treatment outcomes of ATV + ABC/3TC in pretreated subjects in the EuroSIDA cohort when started with undetectable plasma HIV-1 viral load (pVL), performing a time to loss of virological response (TLOVR <50 copies/mL) and a snapshot analysis at 48, 96, and 144 weeks. Virological failure (VF) was defined as confirmed pVL >50 copies/mL. We included 285 subjects, 67% male, with median baseline CD4 530 cells, and 44 months with pVL ⩽50 copies/mL. The third drug in the previous regimen was ritonavir-boosted atazanavir (ATV/r) in 79 (28%), and another ritonavir-boosted protease inhibitor (PI/r) in 29 (10%). Ninety (32%) had previously failed with a PI. Proportions of people with virological success at 48/96/144 weeks were 90%/87%/88% (TLOVR) and 74%/67%/59% (snapshot analysis), respectively. The rates of VF were 8%/8%/6%. Rates of adverse events leading to study discontinuation were 0.4%/1%/2%. The multivariable adjusted analysis showed an association between VF and nadir CD4+ (hazard ratio [HR] 0.63 [95% confidence interval [CI]: 0.42–0.93] per 100 cells higher), time with pVL ⩽50 copies/mL (HR 0.87 [95% CI: 0.79–0.96] per 6 months longer), and previous failure with a PI (HR 2.78 [95% CI: 1.28–6.04]). Resistance selection at failure was uncommon. A switch to ATV + ABC/3TC in selected subjects with suppressed viremia was associated with low rates of VF and discontinuation due to adverse events, even in subjects not receiving ATV/r. The strategy might be considered in those with long-term suppression and no prior PI failure.